Learning to love math : teaching strategies that change student attitudes and get results - Willis, Judy. (b, 2010)
Explains how negative attitudes toward math get established in the brain and what teachers can do to turn those attitudes around
includes bibliographical references and index.
Keywords: Electronic books; MATHEMATICS Study & Teaching